MODERN INSTITUTIONAL AUDIT OF EDUCATIONAL ESTABLISHMENTS: TRANSMISSION OF VALUE ORIENTATIONS - Дудка, Тетяна (Mountain School of Ukrainian Carpaty, 2020)
The content of the article analyzes the fundamentals of the influence of Eurocentric vectors on the development of national educational policy, partly marked by the branching of the educational quality assessment scale. The priority is given to the development of a modern institutional audit of educational establishments based on the principles of transparency, openness, independence, and publicity. Attention is drawn to the representative and controlling functions of the National Agency for Higher Education Quality Assurance and the State Education Quality Service of Ukraine, which are intended to diagnose the existing indicator of the quality of the educational activity. In the course of theoretical generalizations, the author defines the concept of “institutional audit of educational establishments” and emphasizes his expositional orientation of education to meet the market needs of highly qualified personnel. To deepen the theoretical generalizations, the consequential regularities of functioning in the time and space of educational establishments are problematized. The results of the definitive analysis of the categories of “quality” and “quality of educational activity” in domestic and foreign scientific achievements of the XX-XXI centuries are presented. The available theoretical formulations of the latter category by the criterion of priority are generalized. Emphasis is placed on the transmission of value orientations, due to the regularity of circulation of the modern institutional audit of educational establishments in space and time. The three-level structure of the institutional audit of educational establishments is represented, reflecting at the level of the object of audit, the content of audit procedures, quality indicators, internal audit (self-assessment), external independent evaluation by authorized persons. The study used systematic, complex, process, axiological, anthropological, activity, normative, and constructive approaches. In the course of the study, a whole range of methods was involved - analysis and synthesis, induction and deduction, comparison, and system analysis. The use of such a wide methodological spectrum made it possible to structure the issue under study with the help of illustration elements, which facilitate the perception of existing theoretical fact.